A multifunctional bistable laminate: Snap-through morphing enabled by broadband energy harvesting. (July 2018) - Lee, Andrew J; Inman, Daniel J
The elastic instabilities associated with buckling in bistable structures have been harnessed toward energy-based and motion-based applications, with significant research toward energy harvesting and morphing. Often combined with smart materials, structural prototypes are designed with a single application in mind. Recently, a novel method of inducing bistability was proposed by bonding two piezoelectrically actuated macro fiber composites in a[ 0 MFC / 90 MFC ] T layup and releasing the voltage post cure to yield two cylindrically stable configurations. Since the macro fiber composites are simultaneously the actuator and host structure, the resulting efficiencies enable this bistable laminate to be multifunctional, with both broadband energy harvesting and snap-through morphing capabilities. This article experimentally characterizes the vibration-based energy harvesting performance of the laminate to enable morphing. Through frequency sweeps across the first two modes of both states, the laminate exhibits broadband cross-well dynamics that are exploited for improved power generation over linear resonant harvesters. Besides single-well oscillations, snap-throughs are observed in intermittencies and subharmonic, chaotic, and limit cycle oscillations. The maximum power output of each regime and their charge durations of an energy harvesting module are assessed. The laminate's capabilities are then bridged by utilizing harvested energy in the charged module to initiate snap-through actuation.